2020
DOI: 10.1002/fsn3.1359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of microcapsules with avocado peel extract and nisin on the quality of ground beef

Abstract: This study evaluated the incorporation of microcapsules containing nisin and avocado peel extract on the shelf life of ground beef. Ten treatments were studied and divided into two groups: one packaged under vacuum and the other in permeable packaging. Each group contained: (a) control, (b) extract, (c) nisin, (d) empty microcapsules (only wall microcapsule system), and (e) microcapsules with extract and nisin. The samples containing the microcapsules presented lower bacterial growth and less oxidation. On day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…5 The rise in pH during the 10-15 days is related to protein degradation and the accumulation of alkaline substances from microbial metabolism. 36 A similar trend was observed in the study by Calderón-Oliver et al, 37 who reported that the pH of vacuum-packed ground beef decreased up to day 8 during refrigerated storage and increased over the following days. The results showed that the trend of pH decrease in the POL extract treatment group was lower than that in the control treatment group (CON) from 0 to 10 days of storage, and the higher the POL extract concentration, the slower the pH decrease.…”
Section: Antibacterial Activity Of Pol Extractsupporting
confidence: 83%
“…5 The rise in pH during the 10-15 days is related to protein degradation and the accumulation of alkaline substances from microbial metabolism. 36 A similar trend was observed in the study by Calderón-Oliver et al, 37 who reported that the pH of vacuum-packed ground beef decreased up to day 8 during refrigerated storage and increased over the following days. The results showed that the trend of pH decrease in the POL extract treatment group was lower than that in the control treatment group (CON) from 0 to 10 days of storage, and the higher the POL extract concentration, the slower the pH decrease.…”
Section: Antibacterial Activity Of Pol Extractsupporting
confidence: 83%
“…also observed a significant reduction in Lactobacillus acidophilus probiotic cells after baking bread. Other researchers also showed increased thermal stability of probiotic bacteria by encapsulation process(Calderón-Oliver et al, 2020).…”
mentioning
confidence: 94%
“…Similarly, Ni did not achieve any significant reduction in microbial counts in the current study. In contrast, other authors have observed reductions in APC in different types of meat when nisin [45], or a combination of nisin with tea polyphenols and chitosan [46], was applied. It should be noted that nisin has been shown to have greater antimicrobial potential in meat preparations when in combination with other substances [47].…”
Section: Microbial Countsmentioning
confidence: 70%